2019
DOI: 10.1037/prj0000373
|View full text |Cite
|
Sign up to set email alerts
|

The role of recovery colleges in supporting personal goal achievement.

Abstract: This study examined the types of goals set, the degree to which goals were achieved, and the factors influencing goal attainment for participants in a Recovery College, a recovery-based mental health education program that uses peer learning advisors to facilitate individual student learning plans. Method: Students of the Recovery College set baseline goals that were rated in terms of importance and difficulty in line with the Goal Attainment Scale (GAS) framework and reviewed at follow-up points. Goals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…These finding suggest that a minimum level of REC participation may be needed to achieve key recovery outcomes. These findings support and are supported by a recent Australian study ( 41 ), in which attending a higher percentage of REC courses was associated with goal achievement. The post-hoc analysis further identified that socio-demographic characteristics were associated with the extent of participation.…”
Section: Discussionsupporting
confidence: 88%
“…These finding suggest that a minimum level of REC participation may be needed to achieve key recovery outcomes. These findings support and are supported by a recent Australian study ( 41 ), in which attending a higher percentage of REC courses was associated with goal achievement. The post-hoc analysis further identified that socio-demographic characteristics were associated with the extent of participation.…”
Section: Discussionsupporting
confidence: 88%
“…Five papers evaluating supported education were identified [46][47][48][49][50] , all of which focused on recovery colleges: a recoverybased mental health education program that uses peer learning advisors to facilitate individual student learning plans 48 and where students are people with lived experience of mental health problems. Two of the studies were quantitative 48,49 and three employed mixed methods 46,47,50 . Three were conducted in the UK 46,49,50 and two in Australia 47,48 .…”
Section: Supported Education (See Table 1)mentioning
confidence: 99%
“…Two of the studies were quantitative 48,49 and three employed mixed methods 46,47,50 . Three were conducted in the UK 46,49,50 and two in Australia 47,48 .…”
Section: Supported Education (See Table 1)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the initial session, the therapist usually, implicitly or explicitly, asks the client to report their goals with regards to treatment (e.g., symptom reduction) and/or wider personal goals (e.g., to have a better relationship with their children; Michalak & Holtforth, 2006). Goal setting has been associated with goal attainment (Webb & Sheeran, 2006) and goal attainment has, in turn, been associated with positive emotions and wellbeing (Wiese, 2007), better therapeutic outcomes (Tryon, 2018;Wollburg & Braukhaus, 2010), and higher personal recovery (Sommer et al, 2019) . However, setting a goal is a necessary but often insufficient step to achieving the desired outcome and research typically finds a considerable gap between intentions (or self-instructions to perform particular behaviors or to obtain certain outcomes, Triandis, 1980) and behavior (Sheeran & Webb, 2016).…”
Section: Assessing and Promoting The Use Of Implementation Intentions In Clinical Practicementioning
confidence: 99%